Online resources and apps to aid self-diagnosis and help seeking in the perinatal period: A descriptive survey of women's experiences. (November 2020) - Mackintosh, Nicola; Agarwal, Shona; Adcock, Kirsty; Armstrong, Natalie; Briley, Annette; Patterson, Molly; Sandall, Jane; (Sarah) Gong, Qian
Abstract: Objective: Assess the role of online resources and apps for women's help seeking and staff's response to concerns in the perinatal period. Design: Online survey. Descriptive analysis of women's use and experiences of digital resources for self-diagnosis and help seeking, drawing on numerical and free-text responses. Setting: Two tertiary referral centres and one district general hospital in two UK geographic locations. Participants: 632 postnatal women, surveyed over a 4 month period. Measurements: Women's access to digital devices; frequency and type of health concerns experienced after 22 weeks' gestation; variability in use and experiences of websites/apps; perceptions of staff's response to concerns after help-seeking. Findings: 1254 women were approached over a 4-month period; 632 participated (response rate: 50%). Women reported a 'mix and match' blended use of digital resources to both learn about, and self-diagnose/self-triage for potential complications in pregnancy as an adjunct to care provided by maternity staff. Over half the participants experienced concerns about themselves or their baby after 22 weeks. The top concern was fetal movements, reported by 62%. Women used 91 different digital resources to help with understanding and decision-making, in addition to seeking support from family, friends and healthcare professionals. Enabling features of staff responses were identified from free-text responses ( n  = 292) by women who sought professional help regarding their health concerns, and influencing factors at clinical, organisational and digital level. Key conclusions and implications for practice: Online information retrieval and digital self-monitoring is increasingly integral to women's self-care during pregnancy and offers opportunities to support escalation of care and shared decision-making. Further work should assess optimal inclusion of this 'digital work' into clinical consultations.